Reflecting on “A Supervision of Solidarity” - Audet, Cristelle T. (Canadian Journal of Counselling and Psychotherapy, 2010)
Vikki Reynolds’ article, “A Supervision of Solidarity,” presents a supervision approach that addresses some challenges of working with clients who live with social injustice and extreme marginalization. The approach foregrounds “collective ethics” in the spirit of fostering sustainable practice within difficult client contexts. In this reflection piece, I view Supervision of Solidarity as an opportunity to reveal and clarify a socially constructed ethics that places the contextual needs of clients at the forefront. Drawing from Reynolds’ example of Don, I highlight process observations of a Supervision of Solidarity gathering that helped to transform Don’s work and to invite a thickening of collective ethics within his professional community. I end with thoughts about accountability and fostering collective ethics outside of the supervision process.